Emerging Multimodel Zirconia Nanosystems for High‐Performance Biomedical Applications. Issue 9 (11th July 2021) - Rathee, Garima; Bartwal, Gaurav; Rathee, Jyotsna; Mishra, Yogendra Kumar; Kaushik, Ajeet; Solanki, Pratima R.
Abstract : Advancement in nanotechnology supports system development to achieve rapid, affordable, and intelligent health management and has raised the urgent demand to explore multimodel affordable metal oxide nanostructures with the features of biocompatible tunable performance and scaled‐up processing. Keeping this as a motivation, zirconia nanostructures (Zr‐NSs) are emerging as nanostructures of choice for advanced biomedical applications due to affordable, scalable production, easy surface modifications, tunable surface morphology, multiphase stability, and acceptability by biological features such as biocompatibility, viability for bioactives, and a high isoelectric point of 9.5. Zr‐NSs, alone and in the form of hybrids, and nanocomposites have demonstrated notable high performance to develop next‐generation biosensors, implanted materials, and bioelectronics. However, their excellent salient features toward high‐performance biomedical system development are not well articulated in the form of a review. To overcome this knowledge gap, herein an attempt is made to summarize state‐of‐the‐art Zr‐NS preparation techniques as per targeted applications, surface functionalization of Zr‐NSs to achieve desired properties, and applications of Zr‐NSs in the field of biomedicine for health wellness. The challenges, possible solutions, and authors' viewpoints considering prospects in mind are also part of this report. Abstract : Herein, advanced high‐performance bio‐medical applications of surface‐functionalized multimodel zirconia nanostructures (Zr‐NSs) are explored. Zr‐NSs (alone or as hybrids) are demonstrating outstanding performance to develop next generation biosensors, implanted materials, and bioelectronics due to affordable scalable production, ease of surface modifications, tunable surface properties, multiphase stability, and acceptable biological features such as a high isoelectric point, biocompatibility, and viability toward bioactives.